Circuito para monitoramento e restabelecimento da tensão elétrica em células a combustível tipo PEM usando curtos-circuitos controlados - Flach, José Auri (2019)
Electricity generation from renewable sources can contribute significantly to mitigate the impacts that non-renewable sources have on nature. Of these, hydrogen power generation is of great interest and can be easily obtained and stored for future use when needed. The objective of this dissertation is to develop a methodology to discover voltage deficiencies of electric power generation and to recover the optimal functioning of individual proton exchange membrane fuel cells (PEMFC). This methodology relates to the individual application of controlled short circuits in cells that present voltage generation below the expected level. The measurement of the electric voltage of each fuel cell is the basis of information about its efficiency and for the application of a suitable algorithm for its rehabilitation. This study uses modeling, simulations and the construction of a prototype for validation tests. As part of this work, a Module for Monitoring and Applying Controlled Short Circuits (MMACC) was developed and assembled to monitor and act upon individual cells within a stack and to be an auxiliary tool in hydrogen study laboratories. During this development, simulations were performed with fuel cell stacks, taking their voltage readings and short circuit applications using an electronic circuit simulator program. The proposed real prototype was validated in a simulation environment using an auxiliary tool to simulate fuel cells acting in the ohmic range. Results were obtained that showed the feasibility of using this prototype to be applied to fuel cell stacks. The results of this dissertation may help in the study of alternatives and optimization of generation strategies applied to individual cells within a stack. The results of this dissertation may assist in the study of alternatives and optimization of generation strategies applied to individual cells within a stack, but there are still scientific challenges to be overcome to increase fuel cell life, detect anomalies and maintain proper efficiency.